2019
DOI: 10.3389/fmars.2019.00531
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Lack of Phytoplankton Biomass in Naturally Iron Fertilized Waters Near Heard and McDonald Islands in the Southern Ocean

Abstract: The Kerguelen Plateau is one of the regions in the Southern Ocean where spatially large algal blooms occur annually due to natural iron fertilization. The analysis of ocean color data as well as in situ samples collected during the Heard Earth-Ocean-Biosphere Interactions (HEOBI) voyage in January and February 2016, surprisingly revealed that chlorophyll a concentrations in waters located close to Heard and McDonald islands were much lower than those on the central Kerguelen Plateau. This occurs despite high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…Ascertaining the exact mechanism of the glacial Fe(II) production was outside the scope of this study. However, glacial flour observed at station 24 (van der Merwe et al, 2019) and high concentrations of non-algal particles (Wojtasiewicz et al, 2019) silicates, as has been demonstrated in previous studies (Shoenfelt et al, 2019). These could be important mechanisms in maintaining the observed DFe(II) and DFe enrichment at Heard…”
Section: Glacial Runoffsupporting
confidence: 61%
See 4 more Smart Citations
“…Ascertaining the exact mechanism of the glacial Fe(II) production was outside the scope of this study. However, glacial flour observed at station 24 (van der Merwe et al, 2019) and high concentrations of non-algal particles (Wojtasiewicz et al, 2019) silicates, as has been demonstrated in previous studies (Shoenfelt et al, 2019). These could be important mechanisms in maintaining the observed DFe(II) and DFe enrichment at Heard…”
Section: Glacial Runoffsupporting
confidence: 61%
“…Ascertaining the exact mechanism of the glacial DFe (II) production was outside the scope of this study. However, glacial flour observed at station 24 (van der Merwe et al, 2019) and high concentrations of nonalgal particles (Wojtasiewicz et al, 2019) may indicate that DFe (II) production was the result of physical weathering of underlaying basalt by the glacier (van der Merwe et al, 2019). High silicate concentrations observed at this site associated with lower salinity water (van der Merwe et al, 2019) may also indicate that physical weathering resulted in mobilization of Fe (II) silicates, as has been demonstrated in a previous study of SO marine sediment cores (Shoenfelt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations